Pancreatic cancer: current options for diagnosis, staging and therapeutic management - Hartwig, Werner; Büchler, Markus W. (Gastrointestinal tumors, 2014)
Background: Pancreatic cancer is characterized by frequently delayed diagnosis and aggressive tumor growth which hampers most of the current treatment modalities. This review aims to summarize the available evidence about the diagnostic and therapeutic aspects of resectable and non-resectable pancreatic cancer therapy. Summary: Embedded in the concept of multimodal therapy, surgery plays the central role in the treatment of pancreatic cancer. With advantageous tumor characteristics and complete tumor resection as the most relevant positive prognostic factors, the detection of premalignant or early invasive lesions combined with safe and oncologic adequate surgery is the major therapeutic aim. Most pancreatic adenocarcinomas are locally advanced or metastatic when diagnosed and need to be treated by the combination of surgery and (radio)chemotherapy or by palliative chemotherapy. Key Message An interdisciplinary, multimodal approach to therapy is critical for improving the outcomes of patients with pancreatic cancer. Practical Implications Cross-sectional imaging techniques (such as contrast-enhanced multidetector computed tomography) are useful for assessing tumor resectability. For localized, non-metastatic, resectable tumors, the necessity of preoperative biopsies remains controversial. Important prognostic parameters are tumor size, invasion of surrounding tissue, lymph node metastasis and distant metastasis. Various classification systems based on the TNM system have been used for tumor staging and prognosis. The presence of distant metastases is regarded as non-resectable disease, requiring chemotherapy as first treatment. The definition of borderline resectable tumors is still under debate, although a recent definition has been provided by an expert consensus statement. Standard lymphadenectomy is the recommended procedure in pancreatoduodenectomy, based upon the guidelines of the International Study Group of Pancreatic Surgery (ISGPS). Adjuvant chemotherapy is applied in generally all cases of pancreatic ductal adenocarcinoma following macroscopic complete tumor resection. The benefits of adjuvant chemoradiotherapy or immunochemoradiotherapy, or neoadjuvant therapy, however, remain a matter of controversy. For palliative treatment gemcitabine monotherapy is widely used; the FOLFIRINOX protocol provides an alternative for a minority of patients.